Modeling the response of Japanese quail to intake - Sousa, Manoela [UNESP]; Lima, Michele [UNESP]; Vieira, Rita Brito [UNESP]; Pavanini, Jaqueline [UNESP]; Peruzzi, Nelson Jose [UNESP]; Raimundo, Erikson [UNESP]; Santos, Daniel [UNESP]; Silva, Edney [UNESP] (Peerj Inc, 2022)
Background. Understanding how Japanese quails respond to arginine intake has been an objective that previous studies have not fulfilled. The main responses to be quantified include the arginine requirement for maintenance (mg/kg0.67) and egg mass production (mg/g). Quantifying maintenance and production relationships are essential steps for predicting animal response. The current study aimed to describe how quails respond to arginine intake and determine arginine requirements for maintenance and egg production in Japanese quails. Methods. The experiment was carried out in a completely randomized design, with seven treatments and seven replicates with individual birds as experimental units. The arginine levels were: 2.43, 3.64, 4.85, 6.07, 9.07, 12.13, and 14.56 g/kg. The experiment lasted for eight weeks. The variables analyzed were daily arginine intake, daily arginine deposition in eggs, and body weight. The data were analyzed using a mixed model, with the experimental unit being the random effect and the experimental levels of arginine as a fixed effect. When the effect of arginine levels was detected (P < 0.05), saturation kinetics and an exponential model with four parameters (monomolecular) were adopted. ANOVA results indicated that dietary arginine levels significantly affected (P < 0.01) the analyzed variables. The formulation strategy of the experimental diets allowed amplitude in the dietary arginine levels, and according to bird responses, arginine was the limiting nutrient. Results. The arginine requirement for body weight maintenance (BW0.67) was esti-mated to be 90 mg/kg BW0.67 by the monomolecular function. The requirement for egg mass (EM) production was estimated to be 25 mg/g per egg. A factorial model was parameterized as follows: daily arginine intake mg/bird = 90 x BW0.67 + 25 x EM f 12 mg. The model was applied to data obtained from literature, and the resultant error was within the expected limit of 12 mg. The recommended daily arginine intake for the daily production of 11 g of egg and 180 g of BW was determined to be 304 mg/bird. The current study provides procedures that researchers can easily adopt.
Keywords: Arginine; Japanese quail; Modeling; Requirement; Maintenance